2005
DOI: 10.1016/j.amjhyper.2005.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Treatment, and Control of Chest Pain Syndromes and Associated Risk Factors in Hypertensive Patients

Abstract: Primary care physicians treat cardiovascular risk factors relatively aggressively in hypertensives with CPS. However, substantial numbers of these patients do not reach goal levels. Demographic differences in treatment represent opportunities to reduce disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Evaluation of women with symptoms suggestive of IHD is hampered by the definition of “typical” angina, derived from largely male populations where exertional components are more reflective of male patterns of presentation (85-86). Women report more angina despite lower rates of obstructive CAD (11,87-89).…”
Section: Symptom Assessment and Prevalence Of Ischemia In Womenmentioning
confidence: 99%
“…Evaluation of women with symptoms suggestive of IHD is hampered by the definition of “typical” angina, derived from largely male populations where exertional components are more reflective of male patterns of presentation (85-86). Women report more angina despite lower rates of obstructive CAD (11,87-89).…”
Section: Symptom Assessment and Prevalence Of Ischemia In Womenmentioning
confidence: 99%
“…Among all patients in both diagnosis groups, men received more prescriptions than women for eight of the 12 medication classes of interest-all except ARBs, CCB-Ds, CCB-NDs, and diuretics. Among hypertensive, dyslipidemic patients with angina, men received significantly more prescriptions than women for seven of the 12 16,29 Given that this was a population at risk (hypertension and dyslipidemia) and high risk (hypertension, dyslipidemia, and angina) for CV events, the finding of substantial gender and age group differences ACE=angiotensin-converting enzyme; CCB=calcium channel blocker; D=dihydropyridine; *percentage of patients receiving each, shown as 95% confidence intervals (CIs); **significant differences between CIs, p<0.05…”
Section: Resultsmentioning
confidence: 99%
“…The sex of the patient may also influence treatment decisions in pain management. In contrast to the observation that female patients use more analgesics than males, it has been frequently reported that women receive less pharmacological and invasive therapies for their pain complaints . Raftery et al .…”
Section: Discussionmentioning
confidence: 98%